Construção de uma escala de percepção auditiva para adultos: estudos psicométricos preliminares - Peixe, Bruna Pias (2023)
Currently, many studies demonstrate the relevance of collecting self-reported complaints from patients, both for the diagnostic process and for auditory rehabilitation. This study aimed to build a new tool, the Auditory Perception Scale (APS), to be used in the assessment of the adult population, as well as to seek evidence of validity and reliability and to generate reference values for this instrument. Initially, for content validity, the behavioral items of the Auditory Functioning Scale were sent to five expert judges in the area of audiology, so that they could be evaluated by them, as well as the scale's response mode. After the first considerations, the authors forwarded it again, already with appropriate language and content, to be judged. Finally, the last version of the protocol was sent to five non-specialist judges, members of the research target audience. After completing the construction of the Auditory Perception Scale, the pilot sample selection procedures began. Young adults aged between 18 and 44 years old, with preservation of neuropsychological skills, hearing thresholds within normal range, tympanometric curve A, and at least nine years of schooling were included. All participants performed the behavioral tests: Dichotic Digits Test, Frequency Pattern Test, Gap in Noise, Speech in Noise and Masking Level Difference, to assess the normality or alteration of central auditory processing, in addition, they answered the Auditory Perception Scale. At the end of the content validity, the new instrument resulted in a protocol of ten items related to auditory behavior, of quick and easy application, since the ten members of the pilot sample showed ease in answering the scale. For the reliability analysis, 30 adults with normality or central auditory processing disorder were included in the sample, who answered the scale in two different moments (20 days apart). For criterion validity, the same sample was separated into two groups, according to the results of the central auditory processing assessment. The separation occurred so that the performance on the scale could be compared between them. The reliability analysis showed good reliability (Pearson r=0.825), but the comparison between the groups' performances did not show a statistically significant difference (p-value=0.37), not being considered satisfactory. The mean values found in the group with normal central auditory processing were recommended as a reference.